Effect of Smoking on Serum Level of Some Mineral - Ibraheem, Q. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Cigarette smoke contains a lot of toxic and oxidizing materials which causes body toxicity and reduces antioxidant that results in many diseases. In this study, levels of Zinc and Copper (which are antioxidant) were measured in serum of smokers and nonsmokers. It was found that the level of Zinc in serum of smokers was significantly lower than nonsmokers because nitric oxide which is one of cigarette contents acts to increase zinc loss, also a significantly lower copper levels were found in smokers than nonsmokers due to consumption of copper in reducing cadmium toxicity which is a cigarette smoke content